CALCULATION OF AEROTAXI SERVICES (Perner's Contacts, 2016)
The paper investigates way of calculating aerotaxi services with consideration of time value. Calculation considers variables and define their possible values. Methodology of aerotaxi service cost calculation is also applicable for traditional air transportation and transportation by car. Conclusion of the paper is comparison among various alternative way of transportation on chosen route.
Keywords: Aerotaxi service; time value; alternate way of personal transport